Uso de la meteorología en el combate de enfermedades fitopatógenas - Jiménez Otárola, Francisco; Fuentes G, G.; Monge Nájera, J.; Jiménez Otárola, Francisco (2014)
2 gráf. 9 tab. Bib. p. 121-125. Sum. (Es)